Does financial innovation improve performance: Case study of Turkey - Tarana Azimova (Cogent Economics & Finance, 2021)
The mutual funds' performance over time can be driven by a number of dynamic determinants including financial innovation. In fact, financial innovation can be considered as a key factor for improving the performance and increasing the profitability of mutual funds. The purpose of this study is to examine the process of financial innovation in Turkey and its role in accelerating the development and improvement of the performance of the mutual funds industry. This study provides a framework to analyze and evaluate the developments in financial practices over the eight-year period from 2011 to 2018. The process of financial innovation is defined as new financial products and services. Based on panel analysis it is observed that the activity of mutual funds responded to a great extent to innovative market forces.
Keywords: 330; financial innovation; Mutual funds' performance; panel analysis